Optimizing the Number of Curved Turbine Blades on Flettner Rotors for Sustainable Ship Propulsion Without Fuel - Habiburrahman, Novan; Triawati, Indri (Program Studi Teknik Mesin Universitas Pamulang, 2026)
The use of vertical rotating cylinders based on the Magnus effect as an alternative propulsion system for ships has been explored since the early 20th century. By harnessing lateral wind, such rotors are capable of generating thrust to replace conventional sails while simultaneously reducing fossil fuel consumption. However, the efficiency of conventional Flettner rotors remains limited due to their reliance on an external energy supply from driving motors. The novelty of this study lies in the development of a Flettner rotor integrated with quarter-circular blades mounted coaxially to enable self-rotation. This design differs from previous studies that predominantly employed half-circular blades or full rotors, and it is expected to enhance the power coefficient (????ₚ) and torque coefficient (????ᵥ) while maintaining more compact dimensions. This research aims to determine the optimal configuration of blade numbers (2, 4, 8, and 16) and aspect ratio (AR) that delivers superior aerodynamic performance for ship propulsion applications. An experimental approach was conducted using wind tunnel testing of scaled models. Variations in blade number were evaluated based on key performance parameters, including rotor speed, torque, thrust, and the coefficients ????ₚ and ????ᵥ. Data acquisition employed RPM sensors, load cells, and a microcontroller-based system. Statistical analysis was applied to compare each blade configuration against the initial hypothesis that increasing the number of blades improves rotor performance up to a certain limit, beyond which excessive blade numbers reduce efficiency due to increased drag. The findings of this research are expected to contribute to the advancement of more efficient, autonomous, and sustainable ship propulsion systems through the use of a Flettner rotor driven purely by wind energy.